ADJECTIFS HÉRITÉS DU LATIN À VALEUR ADVERBIALE EN ISTRO-ROUMAIN - Adrian CHIRCU (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
Latin inherited Adjectives used as Adverbials in Istro-Romanian. Our study aims to research the adverbial use of adjectives (followed or not by prepositions) inherited from Latin into Istro-Romanian, one of the South-Danubian Romanian dialects which is threatened nowadays with extinction, as foreseen by the majority of linguists interested in this dialectal variety of the Romanian language. In order to pursue an objective analysis we will rely generally on the standard Romanian language and on the description of Istro-Romanian adjectives and adverbs according to specialized literature (treaties, monographies, further studies, dictionaries, glossaries, dialectal texts and so on) as proof for our research, but we will also rely on Latin as well as other Romance languages. We would also like to highlight that such a research has not been undertaken until the present moment. Our research will have an impact not only on the description of a particular aspect discovered in Istro-Romanian, but also on Romanian as a whole or on the Neo-Latin languages, by pointing out certain language-specific structural concordances.